Evaluation of sustainability in horticultural farms of Salto - Aguirre, S.; Chiappe, M. (Agrociencia Uruguay, 2009)
Next to the city of Salto (Northwest of Uruguay), horticultural systems named «de primor» (first season) or «counterseason», which involve highly costly technological packages, have been developed. The adoption of technology by some enterprises has led to the co-existence of large capitalized enterprises with small and medium-size family farms with great endebtedness problems. The last ones are implementing diverse strategies (from more «conventional» to more «organic») to attempt the preservation their plots and overcome the situation. In this study, sustainability strategies are characterized and evaluated from a broad perspective, including economic, productive, environmental and social aspects. Through the adaptation of the Methodological framework, for the Evaluation of natural resource management Systems incorporating Indicators of Sustainability (MESMIS) it is sought to identify the main strengths and weaknesses of the different production systems, in order to generate and recommend valid alternatives for family production.